1972
DOI: 10.1121/1.1913236
|View full text |Cite
|
Sign up to set email alerts
|

Tympanic-Membrane Vibrations in Human Cadaver Ears Studied by Time-Averaged Holography

Abstract: Tympanic-membrane (TM) vibrations were studied in fresh human-cadaver specimens by means of timeaveraged holography. As with an earlier study in cats IS. M. Khanna and J. Tonndorf, J. Acoust. Soc. Amer. 51, 1904 (1972) ], the findings supported the curved-membrane hypothesis of Helmholtz. Despite a careful search for experimental artifacts, no satisfactory explanation was found to account for the fact that the present results are at variance with the stiff-plate concept of yon B(•k6sy. With respect to their q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
3
8

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(100 citation statements)
references
References 6 publications
7
82
3
8
Order By: Relevance
“…The pioneering measurement of the full-field TM motion in human temporal bones was reported by Tonndorf and Khanna (1972) using time-average holography. Recently, the full-field TM surface motion was measured using the multi-point LDV measurement (Fay et al 2005;Maftoon et al 2013), timeaverage Rosowski et al 2009) or stroboscopic holographic interferometry ; Del Socorro Hernandez-Montes et al, Cheng et al 2010Cheng et al , 2013Rosowski et al 2011), optical coherence tomography (Djalilian, et al 2008), and scanning laser Doppler vibrometry (Huber et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering measurement of the full-field TM motion in human temporal bones was reported by Tonndorf and Khanna (1972) using time-average holography. Recently, the full-field TM surface motion was measured using the multi-point LDV measurement (Fay et al 2005;Maftoon et al 2013), timeaverage Rosowski et al 2009) or stroboscopic holographic interferometry ; Del Socorro Hernandez-Montes et al, Cheng et al 2010Cheng et al , 2013Rosowski et al 2011), optical coherence tomography (Djalilian, et al 2008), and scanning laser Doppler vibrometry (Huber et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Tonndorf and Khanna (1972) and Khanna and Tonndorf (1972) were the first to study vibration patterns of the human and cat TM by time-averaged laser holography, at frequencies up to 5 and 6 kHz, respectively. They observed that, in both species, the maximum displacement happens in the posterior region, and for frequencies beyond 2.5 kHz, the simple low-frequency vibration pattern starts to break up and vibration patterns become more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Igualmente la dimensión y el peso de estos comparados entre fetos, adultos y niños que ha mostrado una sutil variación por crecimiento después del nacimiento (Olsewski, 1990). Los patrones de transmisión de fuerzas y su mecánica han sido también estudiados con modelos matemáticos que reconstruyen las formas particulares de los huesecillos para su posterior procesamiento a través de estudios de elemento finito (Tonndorf & Khanna, 1972;Aycan et al, 1990;Sun et al, 2002, Morris et al, 2004. Parece haber un interés común en la morfología y morfometría de la cadena de oscículos del oído medio en humanos, con fines quirúrgicos, pero también en el diseño y la reconstrucción de implantes electromagnéticos, usando medidas precisas que logran reproducir la transmisión de la energía sonora.…”
Section: Discussionunclassified